Sierra Leone : Third and Fourth Reviews Under the Extended Credit Facility Arrangement, Requests for Extension and Rephasing of the Arrangement, Waivers of Nonobservance of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report ;, 2021)
Following two emergency Rapid Credit Facility disbursements in June 2020 and March 2021 to assist in addressing the impact of the COVID-19 pandemic, the Sierra Leonean authorities are committed to resuming the program supported by the Extended Credit Facility arrangement. The program is an important policy anchor for the authorities, and its main objectives-revenue mobilization, safeguarding financial stability, and addressing external vulnerabilities-remain valid. While an economic recovery is underway, driven by the mining sector, risks to the outlook are considerable and, the risk of debt distress is high but remains sustainable. This is predicated on the authorities' ambitious fiscal adjustment and continued reliance on concessional financing and grants. External vulnerabilities are expected to persist over the medium term.